A Chaotic System With Infinite Attractors Based on Memristor - Wen, Junjie; Wang, Jinpeng (Frontiers in Physics, 2022)
In this article, a memristor chaotic system is constructed by introducing a cosine function flux control memristor. By analyzing the balance of the system, it is found that there are coexisting-attractors, and because of the periodicity of cosine function, the chaotic system has infinite coexisting-attractors. The complexity analysis of Spectral Entropy (SE) and C0 is used in this paper to intuitively show the complex dynamics characteristics of the system. In addition, the introduction of paranoid propulsion also provides more possibilities for the system in engineering applications. Finally, the digital signal processing (DSP) experiment verifies the correctness of theoretical analysis and numerical analysis.